Respostas

2014-05-06T11:55:42-03:00
2x²-4x-12=0 

delta = b²-4ac
delta = (-4)² - 4*2*(-12)
delta = 80

x= (-b+-raíz de delta) / 2*a
x = (-(-4)+- raíz de 80) / 2*2
x' = 3,24 aproximadamente
x'' = -1,24 aproximadamente


1 1 1
2014-05-06T11:59:04-03:00
2x² - 4x-12 = 0

Δ= b² - 4 .a .c
Δ= (-4)² -4 . 2 . (-12)
Δ= (-4)² -8(-12)
Δ= 16 +  96
Δ= 112

√112 = 112 | 2
            56 | 2
            23 | 23
-b+/-√Δ ÷ 2.a  

-(-4)+/-2√23 ÷ 2.2
x' = 4 + 2.√23 ÷ 4
x' = 2.√23

x" = 4 - 2.√23 ÷ 4
x" = 2√23 ÷ 4
x" = √23 ÷ 2
2 2 2